Differential behaviors of silver nanoparticles and silver ions towards cysteine: Bioremediation and toxicity to Phanerochaete chrysosporium. (July 2018) - Huang, Zhenzhen; Zeng, Zhuotong; Chen, Anwei; Zeng, Guangming; Xiao, Rong; Xu, Piao; He, Kai; Song, Zhongxian; Hu, Liang; Peng, Min; Huang, Tiantian; Chen, Guiqiu
Abstract: Potential transformations of silver nanoparticles (AgNPs) upon interaction with naturally ubiquitous organic ligands in aquatic environments influence their transport, persistence, bioavailability, and subsequent toxicity to organisms. In this study, differential behaviors of AgNPs and silver ions (Ag + ) towards cysteine (Cys), an amino acid representative of thiol ligands that easily coordinate to Ag + and graft to nanoparticle surfaces, were investigated in the aspects of bioremediation and their toxicity to Phanerochaete chrysosporium . Total Ag removal, 2, 4-dichlorophenol (2, 4-DCP) degradation, extracellular protein secretion, and cellular viability were enhanced to some extent after supplement of various concentrations of cysteine under stress of AgNPs and Ag + . However, an obvious decrease in total Ag uptake was observed after 5–50 μM cysteine addition in the groups treated with 10 μM AgNPs and 1 μM Ag +, especially at a Cys:Ag molar ratio of 5. More stabilization in uptake pattern at this ratio was detected under Ag + exposure than that under AgNP exposure. Furthermore, in the absence of cysteine, all Ag + treatments stimulated the generation of reactive oxygen species (ROS) more significantly than high-dose AgNPs did. However, cysteine supply under AgNP/Ag + stress aggravated ROS levels, albeit alleviated at 100 μM Ag +, indicating that the toxicity profiles of AgNPs and Ag + to P. chrysosporium could be exacerbated or marginally mitigated by cysteine. The results obtained were possibly associated with the lability and bioavailability of AgNP/Ag + -cysteine complexes. Graphical abstract: Highlights: Bioremediation and AgNP/Ag + toxicity were dependent on Cys:Ag ratio to some extent. More stability in Ag uptake was induced by cysteine under stress of Ag + than AgNPs. Cysteine supply aggravated or marginally mitigated ROS level under AgNP/Ag + stress. Distinction was related to lability and bioavailability of Ag-cysteine complexes.